Implementasi Penilaian Kinerja Dalam Pembelajaran Matematika Berbasis Lesson Study pada SMP Muhammadiyah 1 SukoharjoTahun Ajaran 2016/2017 - Januar Heruningsih, Riya, Dr. Sumardi, M.Si (2017)
This research aimed to determine: (1) the readiness of teachers of SMP Muhammadiyah 1 Sukoharjo on performance appraisal, (2) the process of making an assessment instrument performance in mathematics, (3) the application of the implementation of performance assessment in mathematics-based lesson study. (4) constraints implementation of performance assessment in math learning-based lesson study. This qualitative descriptive study was conducted in SMP Muhammadiyah 1 Sukoharjo with research subjects are students of class VIII C totaling 36 students. Data collection techniques used include interviews, observation, testing, and FGD. Data analysis techniques used in the study of data collection, data reduction, data presentation and conclusion. The results showed: (1) teacher at SMP Muhammadiyah 1 Sukoharjo not yet prepared to carry out the assessment of performance, (2) in instrument making teachers are still confused but as their studies teacher Muhammadiyah 1 Sukoharjo was able to make it, (3) The implementation of performance assessment on learning math lesson study fluctuated based on the value of the average math student and student activity in schools become better over time. (4) Obstacles encountered in the implementation of performance assessment in math learning lesson study is based on the implementation of learning time division, instrument-making performance assessment and learning media such as LCD projectors yet.